DETERMINANTS OF PROFITABILITY OF CONVENTIONAL COMMERCIAL BANKS IN INDONESIA FOR THE 2018–2020 PERIOD - Anang Aryokho; Muji Gunarto; Isfarudi Isfarudi (International Journal of Social Science, 2023)
This study aims to examine the effect of CAR, NPL, BOPO and LDR on ROA of Conventional Commercial Banks listed at OJK in 2018-2020. The population and sample in this study were 77 conventional commercial banks with a sample of 231 observational data. The type of data used is secondary data on banking annual financial reports published at OJK for 2018-2019. The sampling technique used purposive sampling technique with panel data regression analysis method with Eviews 10 analysis tool. The results showed that CAR had a positive and significant effect on ROA, NPL and BOPO had a negative and significant effect on ROA, and LDR had a positive but not significant effect on ROA. significant to ROA